Laser Structuring of Polyamide Nanofiber Nonwoven Surfaces and Their Influence on Cell Adhesion. Issue 12 (3rd September 2022) - Michler, Nicole; Götze, Marco; Kürbitz, Tobias; Cepus, Valentin; Schmelzer, Christian E. H.; Hillrichs, Georg; Heilmann, Andreas
Abstract: Electrospun nonwovens have great potential for biomedical applications. They can be used, for example, to mimic the structure of the extracellular matrix of biological tissue. In this work, it is demonstrated that the surface properties of nanofiber nonwovens made of biocompatible and very slowly biodegrading polyamide can be modified by UV picosecond laser processing. Basically, the nanofiber structure is only slightly changed by the corresponding laser process. Significant laser‐induced material change occurs only along narrow lines determined by the scanning process. The newly formed surface structures resemble a bulk surface. It is shown that the growth of mammalian chondrocyte cells (SW1353) is initially more effective on the laser‐processed surface. Cell growth occurs preferably along the laser‐generated lines. After several days of cell growth, an extended layer of cells is formed over the laser‐modified and unmodified surface sections. Thus, laser‐based surface modification provides another tool to affect cell proliferation on polyamide nanofiber nonwovens. Abstract : Due to their outstanding properties and their similarity to extracellular matrix (ECM), electrospun nonwovens have great potential for biomedical applications. In this work, surface structuring of electrospun Polyamide 6 nanofiber nonwovens by laser ablation is reported. The influence of the surface topography on the proliferation of human chondrosarcoma cells (SW1353) is demonstrated.